PENANAMAN NILAI KARAKTER PADA PESERTA DIDIK SMA NEGERI 2 SIPORA, KABUPATEN KEPULAUAN MENTAWAI - Nazmi, Ranti; Azwar, Azwar; Hidayah, Ahmad; Saputra, Hanafi (PUBLICA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Character education is very much needed for today's young generation. This is caused by the progress of the times whose impact is increasingly being felt on changes in the character or behavior of Indonesia's younger generation. Law Number 20 of 2003 also mandates to create students with noble character or morals. This is the basis for this community service activity. This service activity is carried out through several stages, namely (1) needs analysis; (2) work plan; (3) implementation of activities and (4) evaluation. The final result of this community service activity is an increase in the understanding of Sipora 2 Public High School students about the importance of character in responding and continuing life activities in the future.